2022
DOI: 10.1002/jmor.21484
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of tumor suppressors arhgap28 and retinoblastoma in the lizard Podarcis muralis suggests that they contribute to the regulated regeneration of the tail

Abstract: Tail regeneration in lizards is an outstanding and unique postembryonic morphogenetic process. This developmental process is regulated by poorly known factors, but recent studies have suggested that it derives from a balanced activity between oncoproteins and tumor suppressors. Transcriptome and expression data have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The transcriptome and some expression studies conducted on the regenerating blastema-cones of P. muralis have found that among the main oncogenes exclusively activated in the tail, but not in the limb, are 5-6 members of the Wnt and FGF/EGF pathways and a number of noncoding RNAs (snora e scarna; Vitulo et al, 2017a). The main 4 ncRNAs detected in the tail blastema, snord63, snord74, scarna11 are up-regulated in various tumours and only snord26 may function as tumour suppressor (Alibardi, 2019a(Alibardi, , 2022Vitulo et al, 2017a). C-myc and telomerase are also activated in some cells a few days after tail amputation (Figure 2k).…”
Section: Resembles a Tumour-like Stagementioning
confidence: 99%
See 4 more Smart Citations
“…The transcriptome and some expression studies conducted on the regenerating blastema-cones of P. muralis have found that among the main oncogenes exclusively activated in the tail, but not in the limb, are 5-6 members of the Wnt and FGF/EGF pathways and a number of noncoding RNAs (snora e scarna; Vitulo et al, 2017a). The main 4 ncRNAs detected in the tail blastema, snord63, snord74, scarna11 are up-regulated in various tumours and only snord26 may function as tumour suppressor (Alibardi, 2019a(Alibardi, , 2022Vitulo et al, 2017a). C-myc and telomerase are also activated in some cells a few days after tail amputation (Figure 2k).…”
Section: Resembles a Tumour-like Stagementioning
confidence: 99%
“…The observation that a regenerating blastema rapidly elongates into a differentiated tail and not into a tumorigenic outgrowth has further indicated that strict and efficient mechanisms of control in cell proliferation are present in lizard tissues. Therefore, it has been proposed that the growth of the lizard blastema is regulated by the balanced action of oncogenes and tumour suppressors, a mechanism that may have evolved only in lizards among terrestrial vertebrates (Alibardi, 2021a(Alibardi, , 2022.…”
Section: Resembles a Tumour-like Stagementioning
confidence: 99%
See 3 more Smart Citations